2002
DOI: 10.1097/00024720-200210000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Lumbar Interbody Fusion Using rhBMP-2 With Tapered Interbody Cages

Abstract: In a multicenter, prospective, randomized, nonblinded, 2-year study, 279 patients with degenerative lumbar disc disease were randomly divided into two groups that underwent interbody fusion using two tapered threaded fusion cages. The investigational group (143 patients) received rhBMP-2 on an absorbable collagen sponge, and a control group (136 patients) received autogenous iliac crest bone graft. Plain radiographs and computed tomographic scans were used to evaluate fusion at 6, 12, and 24 months after surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
429
1
19

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 646 publications
(463 citation statements)
references
References 21 publications
6
429
1
19
Order By: Relevance
“…The culmination of this strategy for spinal fusion surgery involves harvesting bone from the iliac crest. Limitations of this approach include donor site morbidity, increased operative time and increased blood loss, not to mention the economic derivative summed in the separate limitations [3,13].…”
Section: Introductionmentioning
confidence: 99%
“…The culmination of this strategy for spinal fusion surgery involves harvesting bone from the iliac crest. Limitations of this approach include donor site morbidity, increased operative time and increased blood loss, not to mention the economic derivative summed in the separate limitations [3,13].…”
Section: Introductionmentioning
confidence: 99%
“…The authors of the original industry-sponsored or industry-associated studies of rhBMP-2 all reported the efficacy in applications including both anterior and posterior cervical and lumbar fusion surgery [3][4][5][6][7][8][9][10][11][12][13][14]. Additionally, the authors of these studies stated similar safety profiles with no adverse effects or complications attributable to rhBMP-2 in any study.…”
Section: Introductionmentioning
confidence: 98%
“…Burkus et al (21) 19 Efficacy of calcium sulfate plus decompression bone in lumbar and lumbosacral spinal Alexander et al (22) fusion: preliminary results in 40 patients.…”
mentioning
confidence: 99%
“…envolvendo BMP-2 (5)(6)9,15,17,(20)(21) , três utilizando BMP-7 (10)(11)19) , sete envolvendo biocerâmicas, como hidroxiapatita, fosfato tricálcio e sulfato de cálcio (12)(13)(14)16,18,(22)(23) . O substituto ósseo mostrou-se equivalente ao enxerto autólogo em 19 estudos (4)(5)(6)(7)(8)(9)(10)(11)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) e inferior em três (12,(24)(25) .…”
unclassified
See 1 more Smart Citation